Estudo de caso de acidente e projetos de segurança em prensa industrial - Ishizaki, Guilherme [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
After an accident, in 01/31/2017, involving an hydraulic press at the Foseco's Coatings Cell. A case study was made specifying the possible causes applying the Ishikawa's Diagram to help formulate the hypotheses, then, three points were emphasized: safety sensors were switched off, operator in training and safety locks misaligned. The sensors used have the correct specifications for the type of machine, but from operators' reports the shutdown was due to press locking in many occasions. There weren't any studies to identify the real causes of the locking, so the easiest decision, but inadequate was the shut down without warning the supervisors. This machine use to be operate by the two operators, but in the moment of the accident, it was only one and this one was in training. It was asked to immediately initiate the operation, without checking safety issues or the right qualification of the operator. There was a misaligned at the left safety lock, AISI steel 1020, of around 1 cm, there was made tension analysis and the natural misalignment. The conclusion was that there is a natural misalignment but not significant at first, but taking in consideration that the machine was built 20 years ago, without any maintenance and structural analysis or deterioration apparent on the part. By the regulators standards, specially the NR12, regarding the Machine and Equipment, we could accommodate the cases and it was found many irregularities, as the layout as the operator's qualification. There were made some possible measures to minimize the possibility of the same kind or nature of accidents involving the object of study, using the NR as the base of the projects as the installation of safety handrails at the side ward and light grids at the frontal side by the entrance of the pots. At the back it was more complicated to manage due to lack of ... (Complete abstract, click electronic access below)

Após um acidente, no dia 31/01/2017, envolvendo a prensa hidráulica na célula de tintas da empresa Foseco, foi realizado um estudo de caso levantando as possíveis causas e utilizando o conceito de Diagrama de Ishikawa para auxiliar na formatação do problema. Com isso, foram destacados três pontos de maior importância na resolução: sensores de segurança desligados, operador em treinamento e desalinhamento das travas de segurança. Os sensores utilizados possuem especificação correta para a máquina, porém foi relatado por operadores o desligamento devido ao travamento da prensa em diversas ocasiões. Não foram feitos os devidos estudos para identificar as reais causas do travamento, sendo então tomada a decisão mais fácil, porém errônea de desligar os sensores sem comunicar os superiores do setor e da manutenção. Esta máquina costuma ser operada por dois funcionários e, no momento do acidente, esta era operada por somente um operador e o mesmo em treinamento, foi realizado pedido para operação imediata sem maiores preocupações com a segurança e com o tempo de capacitação correta. Verificou-se um desalinhamento da trava esquerda, aço AISI 1020, de aproximadamente 1 cm, e foram feitas análises de tensões e desalinhamentos naturais. Foi chegado à conclusão de que houve um desalinhamento natural, mas sem expressão aparente, coeficiente de segurança dentro dos parâmetros adequados. Deve-se levar em consideração a falta de manutenção em 20 anos, nunca sendo feitas análises estruturais e de desgaste da peça. A partir das Normas Regulamentadoras, especialmente a NR12, referentes a Máquinas e Equipamentos, enquadramos os casos analisados e foram verificadas diversas irregularidades, tanto no Layout quanto na capacitação dos funcionários. Foram propostas possíveis medidas para mitigar ... (Resumo completo clicar acesso eletrônico abaixo)
Accident case study and safety projects in industrial press
Keywords: Prensas hidráulicas; Segurança do trabalho; Maquinas eletricas; Hydraulic presses